MANAGEMENT OF CURRENT FINANCIAL ASSETS RISK MANAGEMENT IN TRANSPORT COMPANY - Kliestik, Tomas; Birtus, Milos (Doprava a spoje, 2012)
Quantification of risk or risks connected to management and optimization of any current assets components, that is reserves and current receivables, is for a transport company also crucial when current financial assets possession in concerned. This article deals with so called Lambda liquidity index that helps to mange and diversify risks to a certain extent.